Impact of Polymer Molecular Weight on Polymeric Photodiodes. Issue 3 (29th November 2021) - Saggar, Siddhartha; Deshmukh, Kedar D.; McGregor, Sarah K. M.; Hasan, Monirul; Shukla, Atul; Agawane, Jyoti S.; Nayak, Nagaraj; Gann, Eliot; Thomsen, Lars; Kumar, Anil; McNeill, Christopher R.; Lo, Shih‐Chun; et al.
Abstract: The field of organic photodiodes (OPDs) has witnessed continuous development in the last decade. Although a considerable portion of electron‐donating materials are polymers, there has been an existential gap in deciphering the influence of the polymer's molecular‐weight on the photodiode performance. We take up OPDs based on 5, 5′‐[(9, 9‐Dioctyl‐9 H ‐fluorene‐2, 7‐diyl)bis(2, 1, 3‐benzothiadiazole‐7, 4diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone] (FBR) acceptor material blended with three different molecular‐weights of defect‐free form of a well‐known donor polymer poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) are taken up, and their optoelectronic performance along with morphological characteristics are studied. Disparity of up to a decade in key photodetecting characteristics is observed. Further, the tools of near‐edge X‐ray absorption fine‐structure spectroscopy, resonant soft X‐ray scattering spectroscopy, atomic force microscopy, and time‐delayed collection‐field measurements are employed to decipher the difference in the fundamental photo‐physical processes and the operating mechanisms of the OPDs. It is concluded that the molecular weight and the resulting morphology of the active layer strongly influence photodiode performance, in particular, dark current, linear dynamic range, and specific‐detectivity. Abstract : The significant influence of molecular weight of donor polymer on the performance of organic photodiodes has been demonstrated. Difference of up to ten times, in key parameters, such as linear dynamic range, detectivity, saturating intensity, and dark current, is observed. Detailed analysis of morphology and charge transport has been done to further substantiate the results.